Repeated games - Mertens, Jean-François 1946-2012 (Cambridge University Press, 2015)
Three leading experts have produced a landmark work based on a set of working papers published by the Center for Operations Research and Econometrics (CORE) at the Université Catholique de Louvain in 1994 under the title 'Repeated Games', which holds almost mythic status among game theorists. Jean-François Mertens, Sylvain Sorin and Shmuel Zamir have significantly elevated the clarity and depth of presentation with many results presented at a level of generality that goes far beyond the original papers - many written by the authors themselves. Numerous results are new, and many classic results and examples are not to be found elsewhere. Most remain state of the art in the literature. This book is full of challenging and important problems that are set up as exercises, with detailed hints provided for their solutions. A new bibliography traces the development of the core concepts up to the present day
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Game theory; Stochastic processes; Stochastischer Prozess; Spieltheorie